Pengujian Aplikasi E Buk Kades Menggunakan Teknik Boundary Value Analysis dan Equivalence Partitioning - Rahmawati, Aniisah Eka; Endah Wahanani, henni; Prima Aditiawan, Firza (SYNTAX Jurnal Informatika, 2023)
The E Buk Kades application for the DPMD of Jombang Regency is an application that plays an important role in improving the quality of village facilities and infrastructure. Therefore, system testing is needed to ensure that existing applications run according to functionality and find deficiencies in applications so that improvements can be made so that they are more optimal. Testing focuses on the functionality of the application using Black Box Testing with the Equivalence Partitioning and Boundary Value Analysis methods. Based on the test results, it is known that the use of Equivalence Partitioning in the E Buk Kades application is more dominant for testing data entry features, features in the form of options, and in the form of buttons. Meanwhile, Boundary Value Analysis is more dominant in testing features that have a range, such as budget recommendations. Apart from that, from the tests carried out, it can be seen that the Equivalence Partitioning method is more dominant in conducting tests because the features in the E Buk Kades application are dominantly more suitable to be tested with Equivalence Partitioning.